Case Report-Inguinoscrotal ureteral hernia diagnosed on micturating cystourethrography - Sripathi, Smiti; Rajagopal, KV; Kakkar, Chandan; Polnaya, Ashwin (Indian Journal of Radiology and Imaging, 2011)
The presence of a ureter within an inguinal hernia is an extremely rare entity, usually discovered incidentally during herniorrhaphy and may pose a surgical risk. Early preoperative diagnosis is crucial to guide proper surgical approach and to preserve renal function.
Keywords: Hernia; inguinal; ureteral